CCQM-K6.2 Determination of Total Cholesterol in Human Serum - Wise, Stephen A.; Phinney, Karen W.; Duewer, David L.; Sniegoski, Lorna T.; Welch, Michael J.; Pabello, Guiomar; Avila Caldero, Marco A.; Liu Qinde, Liu Qinde; Kooi, Lee Tong; Rego, Eliane; Garrido, Bruno; Allegri, Gabriella; et al. (My University, 2018)
Cholesterol is one of the most frequently measured substances in human blood/serum to assist in assessing the health status of individuals. Because of its clinical significance, CCQM-K6 Determination of Cholesterol in Serum was completed in 2000 as one of the first Key Comparison (KC) studies performed within the Organic Analysis Working Group (OAWG). The first Subsequent KC for cholesterol, CCQM-K6.1, was completed in 2001. Measurements for this second Subsequent, CCQM-K6.2, were completed in 2012. These Subsequent comparisons were conducted to enable CCQM members that had not participated in earlier studies to demonstrate their capabilities to measure a nonpolar (pK(ow) < -2), low molecular mass (100 g/mol to 500 g/mol) metabolite in human serum at relatively high concentrations (1 mg/g to 3 mg/g) found in normal populations. Successful participation in CCQM-K6.2 demonstrated capabilities in analysis of complex biological matrices including sample preparation (extraction, derivatization), LC or GC separation, and quantification using an isotope dilution mass spectrometry approach.